Business Model Canvas : Easy Hot Water / Nur Adiba Lyana Rosli - Rosli, Nur Adiba Lyana (2020)
The measurable and demonstrable benefits obtained by consumers when purchasing Easy Hot Water were identified through value proposition. Firstly, Easy Hot Water is a product that satisfies the need of a small, portable and easy to carry kettle-like appliance. Its function of heating up water either in a cup, a jug or a pot while being small in size as well as light in weight enable consumers to use it anywhere. The product’s performance is highlighted through its ability to boil small amount of water without the need to meet minimum level of water that kettles usually require, ability to take a shorter time in boiling water as compared to other appliances that have the same function and the fact that the product produces no noise when boiling water as kettles tend to be noisy. Easy Hot Water also offers convenience and high usability to the customers. The product is made to be easy to use rather than having complicated procedures, requiring only three steps to fully use the product, to offer convenience and usability as long steps make the product to have a high risk of injury